Innovation Practices in Malaysian Firms: The Case of Two Pharmaceutical Companies - M. Zain Mohamed (Asian Academy of Management Journal, 1997)
Innovation Practices in Malaysian Firms: The Case of Two Pharmaceutical Companies (PDF not available)